Impaired Fluid Intake, but Not Sodium Appetite, in Aged Rats Is Mediated by the Cyclooxygenase-Prostaglandin E2 Pathway - Begg, Denovan P.; Sinclair, Andrew J.; Weisinger, Richard S. (Frontiers in Aging Neuroscience, 2020)
Aging results in decreased fluid intake following dehydration and other dipsogenic stimuli; similar reductions in sodium intake have also been observed with aging. Given that cyclooxygenase (COX)-derived prostanoids are elevated in aged rats in the midbrain and proinflammatory prostanoids are known to decrease fluid intake in dehydrated rats, the aim of this study was to determine if the reductions of fluid intake and sodium intake in aging are mediated by proinflammatory eicosanoid signalling. Therefore, we examined the effect of acute cyclooxygenase (COX) inhibition in adult (4 months-old) and aged (30 months-old) rats prior to ingestive behavior challenges. COX inhibition, using acetylsalicylic acid (ASA), increased fluid intake in aged, but not adult, rats in response to 24-hour dehydration. ASA had no effect on salt intake following sodium depletion and ASA did not change basal fluid or sodium consumption in either age group. Hypothalamic COX-1 and -2, prostaglandin E synthase (PGES) and inducible nitric oxide synthase (iNOS) mRNA expression were all elevated in aged animals, leading to elevated PGE2 levels. COX expression in the hypothalamus was reduced by ASA treatment in rats of both ages resulting in reduced PGE2 levels in aged ASA treated animals. These data indicate that the reduced fluid intake that occurs in aging is due to increased COX-PGE2-mediated inflammation. However, the reduced sodium intake in these animals appears to occur via an alternate mechanism.